2021
DOI: 10.1007/s00284-021-02554-1
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal Transfer of Antibiotic Resistances in Lactobacillus spp.

Abstract: Lactic acid bacteria (LAB) are a heterogeneous group of bacteria which are Gram-positive, facultative anaerobes and nonmotile, non-spore forming, with varied shapes from cocci to coccobacilli and bacilli. Lactobacillus is the largest and most widely used bacterial species amongst LAB in fermented foods and beverages. The genus is a common member of human gut microbiome. Several species are known to provide benefits to the human gut via synergistic interactions with the gut microbiome and their ability to survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 78 publications
(86 reference statements)
0
15
0
Order By: Relevance
“…In fact, the association between the uncontrolled use of antibiotics in human and veterinary medicine and the selection of multidrug-resistant bacteria in humans and cattle has been previously reported [66]. Even though antimicrobial-resistant determinants may be associated with non-pathogenic bacteria, horizontal gene transfer (HGT) events can lead to their transference to pathogenic microorganisms, such as several members of the Enterobacteriaceae family, increasing the prevalence and dissemination of antimicrobial resistance along the food chain [12,68,69]. The likelihood of HGT is even greater if resistance genes are located in mobile genetic elements [70].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the association between the uncontrolled use of antibiotics in human and veterinary medicine and the selection of multidrug-resistant bacteria in humans and cattle has been previously reported [66]. Even though antimicrobial-resistant determinants may be associated with non-pathogenic bacteria, horizontal gene transfer (HGT) events can lead to their transference to pathogenic microorganisms, such as several members of the Enterobacteriaceae family, increasing the prevalence and dissemination of antimicrobial resistance along the food chain [12,68,69]. The likelihood of HGT is even greater if resistance genes are located in mobile genetic elements [70].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have indicated that AMR genes detected in food-LAB can be transferred to commensal bacteria or pathogenic bacteria through HGT, which may pose a serious threat to food safety and public health. The most frequently occurring transfer is that of tetracycline-and macrolideresistance determinants (Flórez et al, 2016;Ojha et al, 2021;Thumu & Halami, 2019;Zarzecka et al, 2020Zarzecka et al, , 2022, but the transference of other resistance genes (aminoglycosides, quinolones) has also been reported (Anisimova & Yarullina, 2020;Jaimee & Halami, 2016). In a recent study by Yasir et al (2020), a total of 36 ARGs and the transposase, integrase, and recombinase genes were detected in LAB isolated from pasteurized and unpasteurized Arabian laban.…”
Section: Safety Evaluationmentioning
confidence: 99%
“…Previous reports have described LAB AMR profiles in detail (Anisimova & Yarullina, 2020; Das et al., 2020; Dušková et al., 2020; Flórez et al., 2016; Guo et al., 2017; Jaimee & Halami, 2016; Moračanin et al., 2017; Ojha et al., 2021; Thumu & Halami, 2019; Yasir et al., 2020; Zarzecka et al., 2020; 2022). There is a wide collection of data reporting intrinsic resistances toward different classes of antimicrobials, namely beta‐lactams, tetracyclines, macrolides, quinolones, aminoglycosides, and glycopeptides (Moračanin et al., 2017).…”
Section: Potential Use Of Non‐starter Lab As Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that the antibiotic resistance gene of LAB could be transferred so that the pathogens developed antibiotic resistance. Researchers have found that antibiotic resistance genes could transfer resistance genes to pathogens through mobile genetic elements such as plasmids, transposons, insertion sequences, and introns and through conjugation pilus, allowing pathogens to acquire antibiotic resistance ( Ojha et al, 2021 ). Conjugation, which is a type of lateral gene transfer, may make pathogens resistant to antibiotics and thus they cannot be eradicated.…”
Section: Safety Of Lab Clinical Treatmentmentioning
confidence: 99%